Farm, wholesale, and retail beef price relationship - Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 1988)
Analysis of weekly retail, wholesale, and farm beef price data indicated that a time lag exists between price changes at the various market levels. Farm-level slaughter cattle price changes typically lead wholesale beef price changes by 2 to 3 weeks. Similarly, wholesale beef price changes typically lead price changes at the retail level by 3 to 4 weeks.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen' s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Wholesale beef prices; Retail beef prices; Farm beef prices